NEW POSSIBILITIES IN THE TREATMENT OF CARDIOVASCULAR DISEASE USING COLCHICINE - M. T. Vatutin; G. S. Smyrnova; E. O. Tselikova (SINAPS LLC, 2016)
The present review of the literature reflects issues of the colchicine's pharmacological properties and mechanism of action. The authors provided the results of a number of scientific studies dedicated to the effects of colchicine on the cardiovascular pathology.